1997
DOI: 10.1590/s0101-81751997000200008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of litter frogs at altitudinal sites at Serra do Japi, southeastern Brazil

Abstract: ABSTRACT. It was sampled the litter frogs at altitudinal sites of a semideciduous mesophytic forest located at SeITa do Japi (Jundiaí, São Paulo, 23°I7'S, 47°00'W, 800-1300m altitude, 1500mm rain/year). Forty two plots of 8x8m were sampled in the dly/cold season of 1995: 21 at a Higher Site (HS) (lOOOm) and 21 at a Lower Site (LS) (850m). The plots were evenly located near, mid-distance, and far from lhe stream-bed. lt was found a total of tive species, three aI each sile. Eleulherodaclylus guenlheri comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1
14

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 5 publications
(3 reference statements)
0
23
1
14
Order By: Relevance
“…High values of dominance, such as those found for P. cuvieri at Uberlândia are typical of seasonally stressed environments, as found in other frog species communities (GIARETTA et al, 1997(GIARETTA et al, , 1999. Our results did not support the expected inverse correlation between specific abundance and body size (DINIZ-FILHO et al, 2004).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…High values of dominance, such as those found for P. cuvieri at Uberlândia are typical of seasonally stressed environments, as found in other frog species communities (GIARETTA et al, 1997(GIARETTA et al, , 1999. Our results did not support the expected inverse correlation between specific abundance and body size (DINIZ-FILHO et al, 2004).…”
Section: Discussioncontrasting
confidence: 86%
“…However, the number of terrestrial frogs found in the Triângulo Mineiro was similar (Boracéia, São Paulo, ca. 29 spp;HEYER et al, 1990) or even larger (GIARETTA et al, 1997(GIARETTA et al, , 1999 than forested localities in southeastern Brazil. Our results call attention to the possibility that the distinguishable rich terrestrial frog fauna of the Atlantic Forest (e. g. Boracéia, HEYER et al, 1990) is due to a disproportional contribution of its riparian species.…”
Section: Discussionmentioning
confidence: 97%
“…Ambientes que sofreram alterações antrópi-cas são caracterizados por vegetação mais esparsa e estão sujeitos a maior exposição solar, menor umidade e temperaturas mais elevadas quando comparados a áreas de mata preservada, com vegetação alta, densa e dossel fechado (Sexton et al 1964, Crump 1971, Inger & Colwell 1977, Pough et al 1977. As características particulares de cada ambiente em relação a estes fatores, possivelmente determinam e limitam a distribuição das espécies presentes no PECB, uma vez que diferentes espécies de anuros respondem diferencialmente às condições ambientais, apresentando diferentes taxas de crescimento e desenvolvimento, além de exibirem graus distintos de resistência e tolerância a perda de água (e.g., Thorson & Svihla 1943, Thorson 1955, Bellis 1962, Heatwole et al 1968, Crump 1971, Snyder & Weathers 1975, Pough et al 1977, Christian et al 1988, Giaretta et al 1997, Werner & Glennemeier 1999, Halverson et al 2003, Felix et al 2004. Espécies do gênero Chaunus, por exemplo, toleram maiores níveis de perda d'água em relação a espécies de outros grupos de anuros (cf.…”
Section: Discussionunclassified
“…The estimated overall frog density of the local leaf litter frog assemblage was relatively high when compared to those found for other sites within the Atlantic Rainforest (Giaretta et al 1997, 1999, Rocha et al 2001, Almeida-Gomes et al 2008, with one exception (Siqueira et al 2009). However, 93% of the frogs found in plots represented a single species, so that the high frog density observed basically reflects the high local abundance of I. parva.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, this small direct-developing frog numerically dominated the anuran assemblage at PED (as also evidenced by the VES methodology). Species with direct development usually are numerically dominant in Neotropical litter frog assemblages (e.g., Scott Junior 1976, Lieberman 1986, Fauth et al 1989, Giaretta et al 1997, 1999, Rocha et al 2001, Siqueira et al 2009, Almeida-Gomes et al 2008. Direct-developing frogs may be more widely distributed within the forest because they are independent of water bodies for reproduction, whereas species with water-dependent reproduction may be limited by the proximity of water bodies (e.g., Heyer & Berven 1973, Scott Junior 1976.…”
Section: Discussionmentioning
confidence: 99%